(3QSGdg aj GdGSJYGPg hGdHSedIs
(3ChdgG (B:s
(3HYO GdHSedI Ef GdCcKQjf GJabhG Ydi Cf hbJ bQGAg GdGSJYGPg eG bHd bQGAI GdaGJMI s
(3BNQgG (B:s
(3jfJgi GdehLhO efgG YfO HOA GdcdGe ai GdaGFOI GdKGdKI ai hLhg GdeOM ai GdOfjG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B60s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQag YGeg (B- (3U (B85 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs